Relationship between vitamin D status and clinical outcomes in dogs with a cranial cruciate ligament rupture. (May 2021) - Clements, Dylan N.; Ryan, John M.; Handel, Ian G.; Gow, Adam G.; Campbell, Susan; Hurst, Emma; Mellanby, Richard J.
Abstract: Cranial cruciate ligament rupture (CCLR) is one of the most common orthopaedic disorders diagnosed in dogs yet the factors which influence postoperative clinical outcomes are poorly understood. Low vitamin D status has been linked to poorer clinical outcomes in human patients undergoing elective orthopaedic surgery. The aim of this study was to examine the relationship between pre-operative vitamin D status, as defined by serum 25 hydroxyvitamin D (25(OH)D) concentrations, and initial disease severity and clinical outcomes in dogs undergoing surgical treatment for a CCLR. Serum 25(OH)D concentrations were measured in 44 dogs with a CCLR on the day before surgery. C-reactive protein concentrations were measured at a median time of 1 day post-surgery and the patient's clinical and radiographic response to CCLR surgical treatment was assessed at a median timepoint of 60 days post-surgery. Serum 25(OH)D concentrations in dogs with a CCLR was not significantly different to a population of healthy dogs (median 74.1 nmol/L and 88.40 nmol/L, respectively). There was no significant correlation between pre-operative serum 25(OH)D concentrations and length of pre-diagnosis clinical signs, pre-operative lameness scores or day 1 post-operative CRP concentrations. Thirty nine of the 44 dogs were re-examined at a median 60 days post-surgery. There was no relationship between the day 60 lameness scores and pre-operative serum 25(OH)D concentrations. In summary, we discovered that the vitamin D status of dogs with a CCLR was not significantly lower than healthy dogs and pre-operative serum 25(OH)D concentrations were not correlated to either pre-surgical disease severity or post-operative clinical outcomes. Highlights: Cranial cruciate ligament rupture (CCLR) is an important disorder in dogs. The factors associated with adverse surgical outcomes are poorly understood. Low vitamin D status is linked to adverse outcomes in human orthopaedic patients. Vitamin D status of dogs with a CCLR was not significantly lower than healthy dogs. Vitamin D status did not correlate to either disease severity or clinical outcomes.